Reading poetry an anthology of poems - DiYanni, Robert (New York Random House School Division, 1989)
A textbook anthology of poems by international authors both classic and contemporary, presented with commentary to develop the ability to read and analyze poetry perceptively.
Includes indexes.
"Copyrights and acknowledgments": p. 447-456.
Keywords: Readers (Secondary); Poetry; English language -- Composition and exercises; Criticism -- Authorship; Poetry -- Collections